(untitled) (Journal of Technology and Operations Management, 2015)
Mobile revolution was converting both developed and developing countries from using ordinary mobile phone to smartphone. This study seeks to identify whatfactors werepersuading Malaysian consumerto purchase smartphone. This studygatheredevidence to support research objective trough quantitative method. Total 427 respondentswere participated in this study.The finding of this study revealsthat multipurpose functionof the smartphone such as multipurpose applications, high speed processors washighlyinfluences Malaysians consumer to purchasethis device.Howeverthe researcher found that the advertisementalso one of the driver that influence Malaysian consumer’sintention to choose specific smartphone.